Relacja kompozytor – muzykolog w twórczości dydaktycznej Mykoły Łastoweckiego - Łastowecka, Zoriana (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2025)
The compositional creativity and musicological works of the modern Ukrainian composer, pedagogue, scientist and music-social activist Mykola Lastovetskyi demonstrate a relation with the socio-cultural needs of both the glocalized musical setting and the regional environment on the example of Drohobych, the city of Lviv region, with its developed cultural and artistic traditions and established musical infrastructure. The didactic orientation of a significant part of the artist’s compositional and musicological work, which appeared in the context of the pedagogical work of M. Lastovetskyi in two leading educational centers of the region – the Drohobych Musical Professional College named after V. Barvinskyi and the Drohobych State Pedagogical University named after I. Franko is noted. The didactic works of the artist include studies devoted to harmony, musical pedagogy, methods of musical education, music theory, analysis of musical forms, solfeggio, instrumental science, application of the latest technologies in the musical and educational process, etc. In general, most of M. Lastovetskyi’s works of, created in Drohobych, can be viewed through the prism of didactic intentions and social demands of the local socio-cultural environment. The composer received orders for the creation of compositions of a certain genre or direction both from the community of the city, church, theater, and from specific performers or teachers. The didactic orientation of the artist’s compositional and musicological work is not only related to his pedagogical activities and the functioning of the city’s musical and educational institutions, but more broadly, directly or indirectly, it reflects performing, touring-concert, competitive, festival, social-public, musical-publishing, cultural and organizational needs of the region.